Síntese e estudo de ancoragem molecular de novos híbridos contendo os núcleos 1,4-naftoquinônico, quinolínico e 1,3,5-triazínico com potencial atividade antineoplásica - Fiorot, Rodolfo Goetze (2015)
Cancer is one of the most feared diseases in society, one of the leading causes of death worldwide. Thus, continuous studies seeking to understand their mechanisms of evolution are essential in order to eradicate it from the body. Although chemotherapy is widely used in virtually all cases of cancer, multidrug resistance tends to decrease the efficiency of the treatment. To solve this problem, the concept of molecular hybridization has been extensively explored between synthetic organic chemicals, in favor of obtaining various drugs that exploit different mechanisms of action. In recent decades, the discovery of signaling pathways overexpressed in cancer cells led to a new approach to therapy with reduced side effects in patients and high efficiency. Among them, the PI3K and AMPK enzymes are noteworthy because they constitute signaling pathways that trigger a lot of other enzymes involved in cancer progress as Akt, mTOR and ERK 1/2. In this context, the present work is based on the synthesis and study of docking using the PI3K and AMPK enzymes as target of molecular hybrids containing the naphthoquinones, quinolines and triazinas cores, with recognized antitumor activity. The docking results showed that most of the proposed hybrids have the receptor/ligand binding interactions greater than the control drugs for their respective enzymes, suggesting inhibition of these signaling pathways as possible target against cancer. In addition, the nature of the interactions and the amino acid residues involved in the formation of the receptor/ligand complex are similar for the drugs control and the proposed candidates, supporting the statement made about the mechanism of action based on the analysis of the magnitude of the interaction energy. Satisfactory results were also achieved in the synthesis of drug candidates: one quinoline-naftoquinonic hybrid 120, one triazine-naftoquinonic hybrid 125 (both unpublished) and one triazine-quinoline 127 hybrid were synthesized.